Mucopolysaccharidosis type II (Hunter syndrome) – A case report - Amit, Agrawal; Jyotsna, Shrivastava (Indian Journal of Case Reports, 2015)
Hunter syndrome or mucopolysaccharidosis (MPS) type II is an X-linked recessive disorder caused by a defect in themetabolism of glycosaminoglycans (GAGs). We present a rare case of MPS with a typical presentation of coarse facies, short stature, mild mental retardation and absence of corneal clouding. His radiographic findings were suggestive of MPS and diagnosis was confirmed by demonstrating deficient Iduronate-2-sulphatase enzyme in plasma. We present this case to highlight the distinctive manifestations as well as radiological and definitive diagnostic findings of the Hunter syndrome.